Effects of Ractopamine hydrochloride are not confined to Mammalian tissue: evidence for direct effects of Ractopamine hydrochloride supplementation on fermentation by ruminal microorganisms - Walker, Callie Elizabeth (Kansas State University, 2009)
Beta-adrenergic agonists, which are synthetic catecholamines, increase rate of gain, improve feed efficiency, and decrease carcass fat, when fed to cattle before slaughter. However, little attention has been given to the potential effects of beta-adrenergic agonists on the rumen ecosystem. Natural catecholamines, such as norepinephrine, epinephrine, and dopamine, have been observed to stimulate bacterial growth. The objectives of this research were to determine if ractopamine hydrochloride (RAC) a synthetic catecholamine has direct effects on growth and fermentation products of ruminal bacteria, and to determine the effects of protein source on ruminal fermentation and proteolysis when cattle are fed RAC. The effects of varying concentrations of RAC on ruminal fermentation were evaluated in vitro. Ractopamine hydrochloride had a quadratic effect on in vitro gas production (P < 0.05). Total VFA production was not changed with RAC (P > 0.50). Different concentrations of RAC were evaluated in vitro with different nitrogen sources to determine effects of nitrogen degradability on response to RAC. There was an interaction between RAC and nitrogen substrate (P < 0.01), with more degradable forms of nitrogen eliciting greater changes in in vitro dry matter disappearance (IVDMD) with RAC supplementation. Significant main effects also were detected for RAC, substrate, and hour (P < 0.001). In vitro analysis of proteolysis revealed that RAC lowered ammonia and amino acid concentrations (P < 0.001). In vivo ruminal ammonia concentrations also were lower when RAC was fed in combination with dry-rolled corn, but not when fed in conjunction with steam-flaked corn (grain processing × RAC, P < 0.01). Addition of RAC, steam-flaked corn, and distiller’s grains (DG) all resulted in lower ruminal ammonia concentrations (P < 0.01). Amino acid concentrations were decreased when RAC was added to diets with DG but were unchanged in diets without added DG (DG × RAC, P < 0.05). Results from these studies suggest that RAC affects fermentation by ruminal microflora. However, there were no differences in growth or fermentative end products of pure bacterial cultures with the addition of RAC (P > 0.10). Overall beta-adrenergic agonists alter ruminal fermentation, which could have important implications for diet formulation.
Keywords: Ractopamine Hydrochloride; Cattle; Ruminal fermentation; Agriculture, Animal Culture and Nutrition (0475)